Multi-Indicator Evaluation of Tile–Wall Integrity Based on Hammering Tests toward Automated Inspection - Li, Yutong; Umeda, Kohichi; Imamoto, Kei-ichi; Sugiyama, Tatsuya; Kiyohara, Chizuru; Sato, Masato; Ohkubo, Takaaki; Sugiyama, Kazuya (Journal of Asian Concrete Federation, 2026)
This study investigates the bonding integrity of exterior wall tiles through hammering tests and multi-domain acoustic feature analysis. Three representative bonding conditions-intact tiles, tile–mortar debonding, and mortar–substrate debonding-were examined. A total of 22 quantitative indicators were extracted from the time-domain waveform, signal envelope, and frequency spectrum to characterize different debonding behaviors. The results show that energy- and amplitude-based indices, such as RMS, Energy, and Crest Factor, effectively distinguish intact and debonded states. Envelope-based parameters, including Envelope Area and Temporal Centroid, reveal the distribution and attenuation characteristics of vibration energy. Frequency-domain features, such as Spectral Centroid, Kurtosis, and Peak Power, capture the distribution, shape, and energy characteristics of the spectral response. The proposed multi-indicator framework provides a quantitative and comprehensive basis for evaluating tile adhesion conditions and contributes to the development of automated hammering-based inspection systems for building façades.